STABILISASI SUHU TUBUH BBLR DENGAN METODE KANGGURU: EVIDENCE BASED CASE REPORT (EBCR) (Jurnal Kesehatan Siliwangi, 2022)
Background: The standard of one's quality of life can be improved by paying attention to the welfare of the mother, one of which is health, which can be started as early as possible since the fetus begins to develop in the womb. Purpose: This research is to maintain body temperature stability in Low Birth Weight Baby. Method: Evidence based case reports (EBCR), using literature searches in several articles, are PubMed and Google Scholar. In the search for E-Data based journals it is limited to 10 year publications, namely in the range 2012 to the latest publication in 2022. Article inclusion and exclusion criteria are, journal searches on E-Data based, in the last ten years (2012-2022), full -text, the research design is a clinical trial, in English or Indonesian. Results: body temperature measurement of 35.5 °C before being given the intervention. Meanwhile, after being given an intervention for 60 minutes, the baby's body temperature was 37.0 °C. Conclusion: The kangaroo method is a natural alternative to stabilizing the body temperature of LBW babies who are at risk of hypothermia.